Project Aid or Budget Aid? The Interests of Governments and Financial Institutions - Carsten Hefeker (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
The paper compares different aid policy instruments and their effect on the target group. Starting from a situation where interest groups compete for the resources of the government, international financial institutions aim to change the policy outcome. They can either directly support one group or condition their financial help to the government on its policy. Apart from a normative analysis which policy is more adequate to help one group, the paper also asks what happens if the IFI is driven by bureaucratic self-interest, and whether this distort policies.
Keywords: F35; O23; D73; 330; aid policy; conditionality; international financial institutions; interest groups